English as a foreign language teachers' perceptions regarding their pedagogical-technological knowledge and its implementation in distance learning during COVID-19. Issue 4 (April 2022) - Meirovitz, Tamar; Russak, Susie; Zur, Ayala
Abstract: With the educational revolution driven by COVID-19, traditional face-to-face teaching methods have rapidly been transformed into accessible, reliable online distance education. This has meant revisiting and reinventing existing technology-based educational processes and models. This study investigates whether teachers of English as a Foreign Language (EFL) are confident that they have the requisite knowledge of how particular technologies are used for remote teaching, both during COVID-19 and as they look to the future. By adopting a mixed-method approach, this paper investigates teacher practices and perceptions regarding teaching online during Covid-19's emergency remote teaching. One hundred and twenty-nine participants were recruited through an online survey. All analyses were carried out using SPSS version 25. Data was based on ranking and non-parametric tests were used. Qualitative data from the open-ended question were analyzed using data-driven thematic analysis. Teachers reported significantly increased reliance on self-teaching, colleagues' knowledge, staff tutorials, and online school support. The gap between knowledge and usage of digital tools was found to be associated with the challenges facing EFL teachers with distance learning. Teachers who reported knowing more or roughly the same about the tools compared to their usage of them knew how to incorporate their knowledge into their practical teaching, took control over the management of their instruction, and had higher pupil engagement and motivation. However, teachers whose knowledge of digital tools was lower than their usage encountered technological difficulties that impaired their teaching. Some implications can be drawn from the study, such as the need for teacher education programs to improve teacher awareness of new pedagogical-technological learning methods, and the importance of providing opportunities to acquire digital competence and encourage teachers to adapt personally to new digital technologies within specific disciplinary contexts. Our findings have both theoretical and practical implications for pre- and in-service teacher training. Abstract : TEFL, Online distance learning, Teachers' professional knowledge, Teachers' perceptions, Teachers' education, Lifelong learning.